Diffractive gratings with varying period’s shape - Jaroszewicz, Zbigniew; Czech, Eugeniusz; Osuch, Tomasz (Photonics Letters of Poland, 2019)
The aim of this short review is to recall various designs of diffraction gratings when the condition of the period’s identity is relaxed and to mention resulting thus some of their applications. Among others the apodization function can be implemented as a variable diffraction efficiency due to the gradual change of the period’s shape. Another possible application is the passive achromatization of the diffraction efficiency of the blazed gratings by randomizing their blaze angle. Full Text: PDF References P. Jacquinot and B. Roizen-Dossier, "II Apodisation", Prog. Opt. 3, 29 (1964). CrossRef H. Bartelt, "Computer-generated holographic component with optimum light efficiency", Appl. Opt. 23, 1499 (1984). CrossRef H. Bartelt, "Applications of the tandem component: an element with optimum light efficiency", Appl. Opt. 24, 3811 (1985). CrossRef N. Château, D. Phalippou, and P. Chavel, "A method for splitting a gaussian laser beam into two coherent uniform beams", Opt. Commun. 88, 33 (1992). CrossRef C.I. Robledo-Sánchez et al. "Binary grating with variable bar/space ratio following a geometrical progression", Opt. Commun. 119, 465 (1995). CrossRef S.Yu. Popov and A.T. Friberg, "Apodization of generalized axicons to produce uniform axial line images", Pure Appl. Opt. 7, 537 (1998). CrossRef S.Yu. Popov et al. "Scientists harvest antibodies from plants", Opt. Commun. 154, 359 (1998). CrossRef J. Albert et al. "Moire phase masks for automatic pure apodisation of fibre Bragg gratings", Electron. Lett. 32 2260 (1996). CrossRef J. Albert et al. "Apodization of the spectral response of fiber Bragg gratings using a phase mask with variable diffraction efficiency", Electron. Lett. 31, 222 (1995). CrossRef Z. Jaroszewicz, A.T. Friberg, and S.Yu. Popov, "Kinoform apodization", J. Mod. Opt. 47, 939 (2000). CrossRef Z. Jaroszewicz et al. "Kinoform apodization by using of programmable diffractive optical elements", Proc. SPIE 5456, 153 (2004). CrossRef F. Trépanier, M. Poulin, and G. Bilodeau, "Complex apodized holographic phase mask for FBG writing", Bragg Gratings, Photosensitivity, and Poling in Glass Waveguides, Technical Digest (Optical Society of America, 2003), paper WC5 CrossRef F .Ghiringhelli, F. Fundamental properties of Bragg gratings and their application to the design of advanced structures, PhD thesis, Univ. of Southampton, (2003). DirectLink T. Osuch, Z. Jaroszewicz, "Numerical analysis of apodized fiber Bragg gratings formation using phase mask with variable diffraction efficiency", Opt. Commun. 284, 567 (2011). CrossRef T. Osuch et al. "Fabrication of phase masks with variable diffraction efficiency using HEBS glass technology", Appl. Opt. 50, 5977 (2011). CrossRef T. Osuch and Z. Jaroszewicz, "Influence of optical fiber location behind an apodized phase mask on Bragg grating reflection efficiencies at Bragg wavelength and its harmonics", Opt. Commun. 382, 36 (2017). CrossRef T. Osuch, "Numerical analysis of the harmonic components of the Bragg wavelength content in spectral responses of apodized fiber Bragg gratings written by means of a phase mask with a variable phase step height", J. Opt. Soc. Am. A 33, 178 (2016). CrossRef Z. Jaroszewicz, T. Osuch, "Harmonic analysis of fiber Bragg gratings written using apodized phase and amplitude masks", Opt. Pura Aplic. 50, 259 (2017). CrossRef N. Davidson, A.A Friesem, and E. Hasman, "Efficient formation of nondiffracting beams with uniform intensity along the propagation direction", Opt. Commun. 88, 326 (1992). CrossRef A.T. Friberg, "Stationary-phase analysis of generalized axicons", J. Opt. Soc. Am. A 13, 743 (1996). CrossRef M. Honkanen, J. Turunen, "Tandem systems for efficient generation of uniform-axial-intensity Bessel fields", Opt. Commun. 154, 368 (1998). CrossRef S.Yu. Popov and A.T. Friberg, "Apodization of generalized axicons to produce uniform axial line images", Pure Appl. Opt. 7, 537 (1998). CrossRef A. Kowalik et al. "Apodised linear axicons", Proc. SPIE 7141, 714125 (2008). CrossRef M.J. Simpson, "Diffractive multifocal intraocular lens image quality", Appl. Opt. 31, 3621 (1992). CrossRef J.A. Davison and M.J. Simpson, "History and development of the apodized diffractive intraocular lens", J. Cataract Refract. Surg. 32, 849 (2006). CrossRef J.C. Alfonso et al. "Prospective visual evaluation of apodized diffractive intraocular lenses", J Cataract Refract Surg. 33, 1235 (2007). CrossRef F. Vega, F. Alba-Bueno, and M.S. Millán, "Energy Distribution between Distance and Near Images in Apodized Diffractive Multifocal Intraocular Lenses", Invest. Ophthalmol. Vis. Sci. 52, 5695 (2011). CrossRef F. Vega et al. "Halo and Through-Focus Performance of Four Diffractive Multifocal Intraocular Lenses", Invest Ophthalmol Vis Sci. 56, 3967 (2015). CrossRef J.P. Guigay, "On Fresnel Diffraction by One-dimensional Periodic Objects, with Application to Structure Determination of Phase Objects", Opt. Acta 18 677 (1971). CrossRef V. Arrizon and J. Ojeda-Castañeda, "Irradiance at Fresnel planes of a phase grating", J. Opt. Soc. Am. A 9, 1801 (1992). CrossRef G. Serrano-Heredia, G. Lu, P. Purwosumarto, and F.T.S. Yu, "Measurement of the phase modulation in liquid crystal television based on the fractional-Talbot effect", Opt. Eng. 35, 2680 (1996). CrossRef Z. Jaroszewicz et al. "Determination of the step height of the binary phase grating from its Fresnel images", Optik 111, 207 (2000). CrossRef L. Martínez-León et al. "Phase calibration of spatial light modulators by means of Fresnel images", J. Opt. A: Pure Appl. Opt. 11, 125405 (2009). CrossRef J.M. Rico-García and L.M Sanchez-Brea "Binary gratings with random heights", Appl. Opt. 48, 3062 (2009). CrossRef R. Brunner, Diffractive optical elements, in Springer Handbook of Lasers and Optics, F. Träger, ed., 2nd ed. (Springer, 2012), pp. 454-461. DirectLink Y. Arieli et al. "Design of diffractive optical elements for multiple wavelengths", Appl. Opt. 37, 6174 (1998). CrossRef Y. Arieli et al. "Design of a diffractive optical element for wide spectral bandwidth", Opt. Lett. 23, 823 (1998). CrossRef B.H. Kleemann, M. Seeßelberg, and J. Ruoff, "Design concepts for broadband high-efficiency does", J. Eur. Opt. Soc. Rapid 3, 08015 (2008). CrossRef T. Gühne and J. Barth, "Strategy for design of achromatic diffractive optical elements with minimized etch depths", Appl. Opt. 52, 8419 (2013). CrossRef H. Lajunen, J. Turunen, and J. Tervo, "Design of polarization gratings for broadband illumination", Opt. Express 13, 3055 (2005). CrossRef H. Lajunen, J. Tervo, and J. Turunen, "High-efficiency broadband diffractive elements based on polarization gratings", Opt. Lett 29, 803 (2004). CrossRef J. Pietarinen, T. Vallius, and J. Turunen, "Wideband four-level transmission gratings with flattened spectral efficiency", Opt. Express 14, 2583 (2006). CrossRef Y. Wang, Y. Kanamori, and K. Hane, "Pitch-variable blazed grating consisting of freestanding silicon beams", Opt. Express 17, 4419 (2009). CrossRef G. Minguez-Vega et al. "Diffraction efficiency achromatization by random change of the blaze angle", Proc. SPIE 4829, 1033 (2002). CrossRef E. Czech et al. "Diffraction Efficiency Achromatization of Blazed Gratings", EOS Topical Meeting on Diffractive Optics 2010, paper 2491. DirectLink E. Czech et al. "Analiza dokładności pomiaru, względnego rozkładu egzytancji widmowej źródeł światła, dokonanego przy użyciu spektroradiometru kompaktowego", Prz. Elektrotech. 91, 171 (2015) (in Polish). CrossRef